Comparison of itraconazole and fluconazole in treatment of cryptococcal meningitis and candida pyelonephritis in rabbits. - Perfect, J R (1986)
Itraconazole and fluconazole, two new triazoles, were examined for their antifungal activity in rabbits. Fluconazole easily crossed the blood-cerebrospinal fluid barrier, and active drug was eliminated in high concentrations in the urine. On the other hand, itraconazole did not cross the blood-cerebrospinal fluid barrier in measurable amounts, and urine concentrations were variable. Despite differences in pharmacokinetics at the site of infection, both agents were equally effective in treating cryptococcal meningitis and candida pyelonephritis in animals. By using a ketoconazole-resistant strain of Candida albicans, we showed that there was cross-resistance in vivo between these two new triazole compounds.